2013
DOI: 10.1002/ccd.25055
|View full text |Cite
|
Sign up to set email alerts
|

Use of regadenoson for measurement of fractional flow reserve

Abstract: Regadenoson is a viable alternative to intravenous adenosine for achieving maximal hyperemia during FFR assessment. Compared to adenosine, regadenoson has a similar hemodynamic response, achieves more rapid hyperemia, is easier to use, and has an excellent side-effect profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…22 Accordingly, regadenoson stress PET MPI showed a good diagnostic accuracy in the detection of obstructive CAD. 23 Recently, it has been demonstrated the evidence for the use of regadenoson as the primary agent for fractional flow reserve measurement 24,25 also in consideration of its effective hyperemia. However, despite the higher myocardial blood flow induced by regadenoson compared to adenosine, 7 these two stressors produce similar pressure-derived fractional flow reserve.…”
Section: Clinical Use or Regadenoson Mpimentioning
confidence: 99%
“…22 Accordingly, regadenoson stress PET MPI showed a good diagnostic accuracy in the detection of obstructive CAD. 23 Recently, it has been demonstrated the evidence for the use of regadenoson as the primary agent for fractional flow reserve measurement 24,25 also in consideration of its effective hyperemia. However, despite the higher myocardial blood flow induced by regadenoson compared to adenosine, 7 these two stressors produce similar pressure-derived fractional flow reserve.…”
Section: Clinical Use or Regadenoson Mpimentioning
confidence: 99%
“…To our knowledge, this is the first study that demonstrates the clinical utility of aminophylline reversal following regadenoson administration for FFR testing. Previous single‐center studies have implemented sequential adenosine infusion followed by IV bolus regadenoson in the same patient during clinically indicated FFR testing in order to evaluate the clinical utility of regadenoson . Each study demonstrated consistency of final FFR values using both pharmacological agents and concluded that regadenoson was a better tolerated and more rapid option compared to weight‐based adenosine infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Aminophylline is a nonselective adenosine receptor antagonist that has been used to reverse the adverse effects of regadenoson, adenosine, and dipyridamole . There have been a small number of studies that describe the use of regadenoson for the assessment of FFR, but none has investigated reversal of regadenoson with aminophylline. The goal of the present study was not only to compare the efficacy of regadenoson to adenosine for the measurement of FFR, but also to assess the impact of aminophylline on the hemodynamics and symptoms following regadenoson bolus.…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant adverse reactions to either drug and REG was overall better tolerated than adenosine. [72] In a more recent study by Prasad et al, [74] the authors compared 57 patients (60 lesions) undergoing FFR measurements first with adenosine followed by a 10 min washout phase and then with REG. They showed high correlation in hyperemic response between the two drugs (R 2 = 0.93) ( Figure 7) and substantially shorter time to peak hyperemia with REG than adenosine as well as a trend to a better side effect profile with REG.…”
Section: Fractional Flow Reserve (Ffr)mentioning
confidence: 99%